PENGUATAN NILAI-NILAI MODERASI MELALUI MANUAL TAFSIR MODERAT DALAM MENANGKAL TAFSIR MANIPULATIF RADIKALIS - Rozi, Achmad Bahrur; Nisa’, Khairun; Jamila, Lailatul (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Religious radicalism as a global threat is now permeating various segments of society as a result of the infiltration of private places by the media, both urban and rural. Radical interpretations that are immediately packaged are freely presented in public places so that they are easily accessible to all levels of society through social media without critical thinking and without comparative material. So far, propaganda for jihadist ideology and succession campaigns continues to move through social media, despite the dissolution of a number of organizations referred to as radicals. This paper aims to describe the implementation of community service in order to promote the values of moderation in order to counter the malign interpretation of radicals groups in East Lenteng Sumenep. The methodology used in this directive is participatory action research (PAR). The use of PAR Is seen as appropriate and viable because it engages the community in all service processes that are expected to be sustainable with the birth of local leaders responsible for continuing assistance after the service program is completed. The results of the service show that awareness of the danger of extremism in religious understanding has begun to emerge and awareness of every form of religious information presented on social media has emerged.